Recommendations on Flood Management at Cengkareng Drain Estuary in Enhancing Estuary Resilience to Compound Hazard - Hastomo, Athena; Anggraheni, Evi; Prasetyo, Adi; Sutjiningsih, Dwita (CSID Journal of Infrastructure Development, 2023)
Jakarta's coastal region, characterized by dense settlements and industrial zones, faces significant flood risks due to land subsidence and rising sea levels, exacerbated by human activities and climate change. This study evaluates the effectiveness of the National Capital Integrated Coastal Development (NCICD) project, which proposes embankments along Jakarta's coast for enhanced flood resilience. Focusing on the Cengkareng Drain estuary, two-dimensional HEC-RAS simulations were employed. This study incorporates various factors such as precipitation, tides, waves, rising sea levels, and land subsidence to model extreme flood scenarios. The analysis reveals key strategies to improve flood management. Firstly, introducing new pumping stations and augmenting existing ones can reduce inundation by 43.16% under present conditions and significantly up to 53.16% by 2050. Secondly, regular dredging to sustain channel capacity is crucial. Additionally, mitigating local land subsidence through stringent law enforcement and heightened public awareness is vital for long-term flood control. These findings offer actionable insights into advancing Jakarta's flood management strategies in the face of evolving environmental challenges.